The Speinshart Recommendations on Generative AI and the EU AI Act - Ahern, Deirdre (Speinshart Reports, 2023)
The Speinshart Recommendation on Generative AI and the EU AI Act INTRODUCTION Recent technological advancements have brought about a significant qualitative transformation in the realm of technology, particularly in the domain of generative AI. The incorporation of specific provisions concerning foundation models and generative AI into the proposed EU AI Act necessitates the compilation of policy-relevant considerations for policy actors and stakeholders, amid the ongoing global discussions on AI regulation and its impacts on people and communities. The well-recognized challenge of regulatory lag, a consequence of rapid technological progress, is juxtaposed with the risk of overly specific regulations that may not remain adaptable over time. Thus, while expressing our broad appreciation for the EU's initiative, as reflected in the latest text ratified by the European Parliament on 14th June 2023, our discourse adopts a principled approach rather than a rigidly rule-based one. This facilitates an in-depth exploration of the socio-technical dynamics of AI systems within diverse sectoral contexts and allows a discussion of best practices ahead of the likely adoption of the EU AI Act in 2024 and with transition period till mid of 2026.
PUBLISHED
Keywords: Creative Technologies; Digital Engagement; Next Generation Medical Devices; Smart & Sustainable Planet; Telecommunications; Regulating artificial intelligence; Globalization; Justice and safeguarding; Legislation; Policy